Canine intrahepatic portosystemic shunt insertion into the systemic circulation is commonly through primary hepatic veins as assessed with CT angiography. Issue 5 (14th July 2020) - Plested, Mark J.; Zwingenberger, Allison L.; Brockman, Daniel J.; Hecht, Silke; Secrest, Scott; Culp, William T.N.; Drees, Randi
Abstract: Congenital intrahepatic portosystemic shunts (IHPSS) in dogs are traditionally classified as right, left, or central divisional. There are few descriptive studies regarding the variation of IHPSS within these categories. This multicenter, analytical, cross‐sectional study aimed to describe a large series of dogs with CT angiography (CTA) of IHPSS, hypothesizing that there would be variation to the existing classification. Ninety CTA studies were assessed for IHPSS type, insertion, and the relationship of the insertion to the primary hepatic veins. Ninety‐two percent of IHPSS inserted into a primary hepatic vein (HV) or phrenic vein, 8% inserted directly into the ventral aspect of the intrahepatic caudal vena cava. The most common IHPSS type was a single right divisional (44%), including those inserting via the right lateral HV or the caudate HV. Left divisional IHPSS (33%) inserted into the left HV or left phrenic vein. Central divisional IHPSS (13%) inserted into the quadrate HV, central HV, dorsal right medial HV, or directly into the ventral aspect of the intrahepatic caudal vena cava. Multiple sites of insertion were seen in 9% of dogs. Within left, central, and right divisional types, further subclassifications can therefore commonly be defined based on the hepatic veins with which the shunting vessel communicates. Relating IHPSS morphology to the receiving primary HV could make IHPSS categorization more consistent and may influence the type and method of IHPSS attenuation recommended.